The importance of botanic gardens for global change research—New insights into Cambridge's hidden truffle kingdom. Issue 3 (27th January 2023) - Centenaro, Giada; Glover, Beverley J.; Piermattei, Alma; Thomas, Paul W.; Čejka, Tomáš; Büntgen, Ulf
Social Impact Statement: Botanic gardens offer unique opportunities for unravelling responses of plant life to climate change. Despite investigations into their aboveground sphere, the belowground realm is usually neglected. Cambridge University Botanic Garden now illuminates the hidden world of one of the most sought‐after culinary delicacies—the Burgundy truffle. The garden's plant diversity, the serendipity of a truffle dog, and our curiosity‐driven research agenda reveal insights into 278 truffle fruitbodies that grew symbiotically with an unusually high number of host species. Our study reinforces the power of botanic gardens to disentangle ecosystem processes and emphasizes the proximity of scientific and public interests in truffles. Abstract : Botanic gardens offer unique opportunities for unravelling responses of plant life to climate change. Despite investigations into their aboveground sphere, the belowground realm is usually neglected. Cambridge University Botanic Garden now illuminates the hidden world of one of the most sought‐after culinary delicacies—the Burgundy truffle. The garden's plant diversity, the serendipity of a truffle dog, and our curiosity‐driven research agenda reveal insights into 278 truffle fruitbodies that grew symbiotically with an unusually high number of host species. Our study reinforces the power of botanic gardens to disentangle ecosystem processes and emphasizes the proximity of scientific and public interests in truffles.